Pinch technology: Supertargetting for optimum synthesis of energy recovery networks - Abdul Manan, Zainuddin; Mutalib, M. I. A. (1992)
Synthesis of optimum energy recovery networks in the context of overall process has been successful through the emergence of Pinch Technology. The procedures apply to energy systems involving heat exchanger networks, heat pumps, combined heat and power schemes (cogeneration) and utility systems. Basic thermodynamics principles are applied to overall process to produce minimum energy targets before network design. Next, a design that satisfies the minimum energy requirements is synthesized by means of a few experienced-based design heuristics and fundamentals of thermodynamics. The result is an approach that has gained success in over 500 industrial applications worldwide. In the beginning of the development pinch Technology, minimum energy is of prime importance while concerns for network capital are largely brought in as an afterthought. An overall approach has recently emerged to bring together energy and capital cost targets before design. Near global optimality of the final design is virtually guaranteed, even for the complex and highly constrained industrial problems. A key concept is that of supertargeting. This paper describes a case study application involving supertargeting and compares the approach to that of the current pinch design method which is based only on energy targets.